Designing a Weight Gain Prevention Trial for Young Adults: The CHOICES Study - Lytle, Leslie A. (2014)
BACKGROUND: Young adults are at risk for weight gain. Little is known about how to design weight control programs to meet the needs of young adults and few theory-based interventions have been evaluated in a randomized control trial. The Choosing Healthy Options in College Environments and Settings (CHOICES) study was funded to create a technology-based program for 2-year community college students to help prevent unhealthy weight gain. The purpose of this paper is to: 1) provide a brief background on weight-related interventions in young adults; 2) describe the study design for the CHOICES study, the conceptual model guiding the research and the CHOICES intervention; and 3) discuss implications of this research for health educators. TRANSLATION TO HEALTH EDUCATION PRACTICE: Our experiences from the CHOICES study will be useful in suggesting other theory-based models and intervention strategies that might be helpful in programs attempting to prevent unhealthy weight gain in young adults. In addition, this paper discusses important considerations for working with 2-year colleges on this type of health promotion work.